2013
DOI: 10.1038/ejhg.2013.184
|View full text |Cite
|
Sign up to set email alerts
|

Sequestosome-1 (SQSTM1) sequence variants in ALS cases in the UK: prevalence and coexistence of SQSTM1 mutations in ALS kindred with PDB

Abstract: Mutations in the SQSTM1 gene have been reported to be associated with amyotrophic lateral sclerosis (ALS). We sought to determine the frequency of these mutations in a UK familial ALS ( Pro392Leu) carriers were heterozygous for a previously reported founder haplotype for PDB, where this mutation has an established causal effect. The frequency of the p.(Pro392Leu) mutation in this UK FALS cohort was 2.3% and 0.97% overall including three previously screened FALS cohorts. Our results confirm the presence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 28 publications
0
38
0
Order By: Relevance
“…To maintain intracellular homeostasis, p62 participates in the degradation of protein aggregates and cytoplasmic bodies via selective autophagy through its PB1, LIR, and UBA domains (30). SQSTM1 has been screened as a candidate gene in eight studies of ALS patients (31)(32)(33)(34)(35)(36)(37)(38).…”
Section: Introductionmentioning
confidence: 99%
“…To maintain intracellular homeostasis, p62 participates in the degradation of protein aggregates and cytoplasmic bodies via selective autophagy through its PB1, LIR, and UBA domains (30). SQSTM1 has been screened as a candidate gene in eight studies of ALS patients (31)(32)(33)(34)(35)(36)(37)(38).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported a splice donor variant in SQSTM1 in a family with an autosomal dominant distal myopathy and also in an unrelated patient with sporadic distal myopathy (Bucelli et al., 2015). In addition, mutations in SQSTM1 are well known to be associated with familial and/or sporadic Paget disease of bone, ALS, and frontotemporal dementia (FTD) (Fecto et al., 2011, Kwok et al., 2014, Laurin et al., 2002, Le Ber et al., 2013, Miller et al., 2015, Rubino et al., 2012). Mutations in valosin-containing protein ( VCP ) gene are known to cause an inherited form of IBM with Paget disease and frontotemporal dementia (IBMPFD) (Gidaro et al., 2008, Watts et al., 2004) and have also been reported in cases with ALS and FTD (Johnson et al., 2010, Koppers et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies failed to confirm the association of VCP [51][52][53][54][55][56] and UBQLN2 [57][58][59][60][61][62][63][64][65][66] with ALS/FTD, suggesting that mutations in these genes are not a common cause of ALS/FTD globally. Conversely, the presence of sequestosome (SQSTM1) mutations in 1-3.5% of ALS/FTD patients has been confirmed [67][68][69][70][71][72][73][74][75]. In 2014, whole-exome sequencing led to the identification of one mutation in the gene coiled-coil-helix-coiledcoil-helix domain-containing protein 10 (CHCHD10) in two families presenting with ALS/FTD [76].…”
mentioning
confidence: 99%